The role of science and technology in sustainable development: A case study in Ho Chi Minh city, Vietnam - Thuy, Pham Thi (Linguistics and Culture Review, 2021)
Science and technology not only improve people’s knowledge by assisting them in perceiving and comprehending the world’s nature and laws, but also by assisting them in transforming knowledge into technical means, or ways to improve the world, thus effectively serving each country’s socio-economic development. Ho Chi Minh City has used its potentials and advantages to seize chances and drive back challenges as part of the international integration process. significant economic, scientific, and technological centers of the country. However, several fundamental issues arise in the growth process in Ho Chi Minh City, such as science and technology failing to match the criteria of the city’s sustainable development; The level of science and technology is still low, the competitiveness is low, and production is still based on manual labor; the science and technology staff is still low, and the team of leading experts in priority science and technology fields, such as biotechnology, nanotechnology, microchip technology, and automation, is severely lacking; planning for the development of high-quality human resources has not been given due attention, and implementation has been fragmented; Many issues and deficiencies in policies on training, developing and employing scientific workers in general, and young scientists in particular, remain unresolved.